ADEN UNIVERSITY STUDENT’S REACTION TOWARD THE TURKISH DRAMA - Ba Yashot, Mohammed Arfan Salem (American International Journal of Social Science Research, 2022)
The main purpose of this study is to investigate the general reaction of the students in Yemen, Aden University, Faculty of Mass Communication, the Turkish drama and the effects of it on the research sample. The results of the research are based on the use of the descriptive approach. Online interviews were conducted with eight students. Among the research sample, there were many reasons to watch Turkish TV series since 2007. The most important of which were raising the importance of social issues, reinforcing national values and increasing the national belongings. It resulted out that the most watched Turkish TV series in Yemen are those series which belong to war and conflict, while women prefer romantic or drama TV series that deal with family and social issues. Turkish TV series have created a good image about Turkey and Turkish people, and there are great similarities between Yemen and Turkey in the culture in some traditions and customs and there are also some differences. Turkish TV series also contributed to the promotion of Turkey in general. JEL Classification Codes: Z13.